2017
DOI: 10.1089/nat.2016.0650
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 2′-O-Methoxyethyl Containing Antisense Oligonucleotides on Platelets in Human Clinical Trials

Abstract: A thorough analysis of clinical trial data in the Ionis integrated safety database (ISDB) was performed to determine if there is a class effect on platelet numbers and function in subjects treated with 2′-O-methoxyethyl (2′MOE)-modified antisense oligonucleotides (ASOs). The Ionis ISDB includes over 2,600 human subjects treated with 16 different 2′MOE ASOs in placebo-controlled and open-label clinical trials over a range of doses up to 624 mg/week and treatment durations as long as 4.6 years. This analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 31 publications
(17 reference statements)
1
72
2
1
Order By: Relevance
“…It has been recently reported that 60% of the anti-PF4/heparin antibodies that induced platelet activation in the presence of heparin also caused platelet activation in the presence of nucleic acids [ 12 , 15 ] which suggests that only some aspects of ON-induced thrombocytopenia may be related to mechanisms leading to HIT and more research is required to delineate this effect. Of note, although the rare documented cases of ON-related thrombocytopenia in humans have generally had a late onset [ 9 ], other features such as dose-dependency and lack of documented thrombosis do not seem to match the HIT model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently reported that 60% of the anti-PF4/heparin antibodies that induced platelet activation in the presence of heparin also caused platelet activation in the presence of nucleic acids [ 12 , 15 ] which suggests that only some aspects of ON-induced thrombocytopenia may be related to mechanisms leading to HIT and more research is required to delineate this effect. Of note, although the rare documented cases of ON-related thrombocytopenia in humans have generally had a late onset [ 9 ], other features such as dose-dependency and lack of documented thrombosis do not seem to match the HIT model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cases of severe thrombocytopenia were reported in two phase 3 trials with 2’-O-methoxyethyl (2’-MOE)-modified phosphorothioate oligonucleotides, IONIS-TTR RX and volanesorsen. These findings triggered an investigation of a clinical safety database of over 2,600 subjects treated with 16 different MOE-ONs [ 9 ]. The analysis—which excluded data from oncology trials as well as the IONIS-TTR RX and volanesorsen trials—concluded that no generic class effect on platelet numbers could be observed and no platelet levels below 50 K/μl were seen in any of the investigated trials.…”
Section: Introductionmentioning
confidence: 99%
“…The FDA recommended that clinicians regularly monitor patients receiving nusinersen for coagulopathy, thrombocytopenia, and proteinuria. The incidence of clinically significant thrombocytopenia, platelet dysfunction, or nephrotoxicity across trials with similarly modified antisense oligonucleotides was very small, 11,14,15 but one patient treated with an antisense oligonucleotide (inotersen) in a study of individuals with familial amyloid polyneuropathy died due to thrombocytopenia-related intracranial hemorrhage. 16 Transient AEs related to intrathecal administration, including headache, vomiting, back pain, and post-LP syndrome, were reported in 40%-50% of patients.…”
Section: Safetymentioning
confidence: 99%
“…A previous publication examined the general side effect profiles of 2′MOE ASOs in NHPs and human normal volunteer studies [ 7 ]. A second publication evaluated the effects of 2′MOE ASOs on number of platelets in completed clinical trials and those with unblinded locked data from analysis of primary end points [ 8 ].…”
Section: Introductionmentioning
confidence: 99%